Class 10 - Mathematics
Introduction To Trigonometry - Exercise 8.4
Top Block 1
Exercise 8.4
Question : 1:Express the trigonometric ratios sin A, sec A and tan A in terms of cot A.
Answer :
(i) sin A = √(sin2 A)
= √(1/coses2 A)
= √{1/(1 + cot2 A)} [coses2 A = 1 + cot2 A]
(ii) sec A = √(sec2 A)
= √(1 + tan2 A) [sec2 A = 1 + tan2 A]
= √(1 + 1/cot2 A)
= √{(1 + cot2 A)/ cot2 A}
= √{(1 + cot2 A)/ cot A
(iii) tan A = 1/cot A
Question : 2:Write all the other trigonometric ratios of ∠ A in terms of sec A.
(i) sin A = √(sin2 A)
(ii) cos A = 1/sec A
(iii) tan A = √(tan2 A)
(iv) cot A = √(cot2 A)
(v) cosec A = √(cosec2 A)
Answer :
(i) sin A = √(sin2 A)
= √(1 – cos2 A)
= √(1 – 1/sec2 A)
= √{( sec2 A – 1)/sec2 A}
= √( sec2 A – 1)/sec A
(ii) cos A = 1/sec A
(iii) tan A = √(tan2 A)
= √(sec2 A – 1)
(iv) cot A = √(cot2 A)
= √(1/tan2 A)
= √{1/(sec2 A – 1)}
= 1/√ (sec2 A – 1)
(v) cosec A = √(cosec2 A)
= √(1 + cot2 A)
= √(1 + 1/tan2 A)
= √{(1 + 1/(sec2 A – 1)}
= √{(sec2 A – 1 + 1)/(sec2 A – 1)}
= √{sec2 A/(sec2 A – 1)}
= sec A/√(sec2 A – 1)
Question : 3:Evaluate :
(i) (sin2 63o + sin2 27o)/(cos2 17o + cos2 73o)
(ii) sin 25o cos 65o + cos 25o sin 65o
Answer :
(i) (sin2 63o + sin2 27o)/(cos2 17o + cos2 73o)
= {sin2 63o + cos2 (90 – 27o)}/{cos2 17o + sin2 (90 – 73o)}
[sin θ = cos(90o – θ) and cos θ = sin(90o – θ)]
= (sin2 63o + cos2 63o)/(cos2 17o + sin2 17o)
= 1
(ii) sin 25o cos 65o + cos 25o sin 65o
= cos(90 – 25o)cos 65o + sin(90 – 25o)sin 65o
= cos 65o cos 65o + sin 65o sin 650 [sin θ = cos(90o – θ) and cos θ = sin(90o – θ)]
= cos2 65o + sin2 65o
= 1 [sin2 θ + cos2 θ = 1]
Question : 4 :
Choose the correct option. Justify your choice.
(i) 9 sec2 A – 9 tan2 A =
(A) 1 (B) 9 (C) 8 (D) 0
(ii) (1 + tan θ + sec θ) (1 + cot θ – cosec θ) =
(A) 0 (B) 1 (C) 2 (D) -1
(iii) (sec A + tan A) (1 – sin A) =
(A) sec A (B) sin A (C) cosec A (D) cos A
(iv) (1 + tan2 A)/(1 + cot2 A) =
(A) sec2 A (B) –1 (C) cot2A (D) tan2 A
Answer :
(i) 9 sec2 A – 9 tan2 A =
Given, 9 sec2 A – 9 tan2 A
= 9(sec2 A – tan2 A)
= 9*1 {since sec2 A – tan2 A = 1}
= 9
Hence, option (B) is the correct answer.
(ii) (1 + tan θ + sec θ) (1 + cot θ – cosec θ) =
= 1 + cot θ – cosec θ + tan θ + tan θ cot θ – tan θ cosec θ + sec θ + sec θ cot θ – sec θ cosec θ
= 1 + cos θ/sin θ – 1/sin θ + sin θ/cos θ + 1 – sin θ/cos θ * 1/sin θ + 1/cos θ
+ 1/cos θ * cos θ/sin θ – 1/cos θ * 1/sin θ [since tan θ cot θ = 1]
= 2 + cos θ/sin θ – 1/sin θ + sin θ/cos θ – 1/cos θ + 1/cos θ + 1/sin θ – 1/(cos θ * sin θ)
= 2 + cos θ/sin θ + sin θ/cos θ – 1/(cos θ * sin θ)
= 2 + (cos2 θ + sin2 θ – 1)/ (cos θ * sin θ)
= 2 + (1 – 1)/ (cos θ * sin θ) [sin2 θ + cos2 θ = 1]
= 2 + 0
= 2
Hence, option (C) is the correct answer.
(iii) (sec A + tan A) (1 – sin A) = (1/cos A + sin A/cos A) (1 – sin A)
= {(1 + sin A)/cos A}(1 – sin A)
= (1 – sin2 A)/cos A
= cos2 A/cos A [sin2 θ + cos2 θ = 1]
= cos A
Hence, option (D) is the correct answer.
(iv) (1 + tan2 A)/(1 + cot2 A) = sec2 A/cosec2 A
[sec2 A = 1 + cot2 A and cosec2 A = 1 + tan2 A]
= (1/cos2 A)/(1/sin2 A)
= sin2 A/ cos2 A
= tan2 A
Hence, option (D) is the correct answer.
Question : 5:Prove the following identities, where the angles involved are acute angles for which the expressions are defined.
(i) (cosec θ – cot θ)2 = (1 – cos θ)/(1 + cos θ) (ii) cos A/(1 + sin A) + (1 + sin A)/cos A = 2 sec A
(iii) tan θ/(1 – cot θ) + cot θ/(1 – tan θ) = 1 + sec θ + cosec θ
[Hint : Write the expression in terms of sin θ and cos θ]
(iv) (1 + sec A)/sec A = sin2 A/(1 – cos A)
[Hint : Simplify LHS and RHS separately]
(v) (cos A – sin A + 1)/ (cos A + sin A – 1) = cosec A, using the identity cosec2 A = 1 + cot2 A.
(vi) √{(1 + sin A)/(1 – sin A)} = sec A + tan A
(vii) (sin θ – 2 sin3 θ)/(2cos3 θ – cos θ) = tan θ
(viii) (sin A + cosec A)2 + (cos A + sec A)2 = 7 + tan2 A + cot2 A
(ix) (cosec A – sin A)(sec A – cos A) = 1/(tan A + cot A)
[Hint : Simplify LHS and RHS separately]
(x) (1 + tan2 A)/(1 + cot2 A) = (1 – tan2 A)/(1 – cot2 A) = tan2 A
Answer :
(i) LHS:
(cosec θ – cot θ)2 = (1/sin θ – cos θ/sin θ)2
= {(1 – cos θ)/sin θ}2
= (1 – cos θ)2/sin2 θ
= (1 – cos θ)2/(1 – cos2 θ) [sin2 θ + cos2 θ = 1]
= (1 – cos θ)2/{(1 – cos θ) (1 + cos θ)} [a2 – b2 = (a – b)(a + b)]
= (1 – cos θ)/{(1 + cos θ)
= RHS
(ii) LHS:
cos A/(1 + sin A) + (1 + sin A)/cos A = {cos2 A + (1 + sin A)2}/{(1 + sin A) * cos A}
= {cos2 A + 1 + sin2 A + 2sin A}/{(1 + sin A) * cos A}
= {1 + 1 + 2sin A}/{(1 + sin A) * cos A} [sin2 θ + cos2 θ = 1]
= {2 + 2sin A}/{(1 + sin A) * cos A}
= 2(1 + sin A)/{(1 + sin A) * cos A}
= 2/cos A
= 2 sec A
= RHS
Mddle block 1
tan θ/(1 – cot θ) + cot θ/(1 – tan θ)
= (sin θ/cos θ)/(1 – cos θ/sin θ) + (cos θ/sin θ)/(1 – sin θ/cos θ)
= (sin θ/cos θ)/{(sin θ – cos θ)/sin θ} + (cos θ/sin θ)/{(cos θ – sin θ)/cos θ}
= sin2 θ/{cos θ(sin θ – cos θ)} + cos2 θ/{sin θ(cos θ – sin θ)}
= sin2 θ/{cos θ(sin θ – cos θ)} – cos2 θ/{sin θ(sin θ – cos θ)}
= (sin3 θ – cos3 θ)/{cos θ * sin θ * (sin θ – cos θ)}
= {(sin2 θ + cos2 θ + sin θ cos θ)(sin θ – cos θ)}/{cos θ * sin θ * (sin θ – cos θ)}
= (1 + sin θ cos θ)/(cos θ * sin θ) [sin2 θ + cos2 θ = 1]
= 1/(cos θ * sin θ) + (cos θ * sin θ)/ (cos θ * sin θ)
= sec θ cosec θ + 1
= RHS
(iv) LHS
(1 + sec A)/sec A = (1 + 1/cos A)/(1/cos A)
= {(cos A + 1)/cos A}/(1/cos A)
= (1 + cos A)/1
= (1 + cos A)/1 * (1 – cos A)/ (1 – cos A)
= (1 – cos2 A)/ (1 + cos A)
= sin2 A/ (1 + cos A) [sin2 θ + cos2 θ = 1]
= RHS
(v) LHS:
(cos A – sin A + 1)/ (cos A + sin A – 1)
= {(cos A – sin A + 1)/sin A}/{(cos A + sin A – 1)/sin A} [divide by sin A]
= (cot A – 1 + cosec A)/ (cot A + 1 – cosec A)
= {cot A + (-1) + cosec A}/ (cot A + 1 – cosec A)
= {cot A + cosec A + cosec2 A – cot2 A}/ (cot A + 1 – cosec A)
= {cot A + cosec A + (cosec A – cot A) (cosec A + cot A)}/ (cot A + 1 – cosec A)
= {(cosec A + cot A) (1 – cosec A + cot A)}/ (cot A + 1 – cosec A)
= cosec A + cot A
= RHS
(vi) LHS:
√{(1 + sin A)/(1 – sin A)} = √[{(1 + sin A)/(1 – sin A)} * {(1 + sin A)/(1 + sin A)}]
= √{(1 + sin A)2/(1 – sin2 A)}
= √{(1 + sin A)2/cos2 A}
= (1 + sin A)/cos A
= 1/cos A + sin A/cos A
= sec A + tan A = RHS
(vii) (sin θ – 2 sin3 θ)/(2cos3 θ – cos θ) = {sin θ(1 – 2 sin2 θ)}/{cos θ(2cos2 θ – 1)}
= {sin θ(1 – 2 sin2 θ)}/{cos θ * 2(1 – sin2 θ) – 1)}
= {sin θ(1 – 2 sin2 θ)}/{cos θ(2 – 2sin2 θ – 1)}
= {sin θ(1 – 2 sin2 θ)}/{cos θ(1 – 2sin2 θ)}
= sin θ/cos θ
= tan θ
= RHS
(viii) LHS:
(sin A + cosec A)2 + (cos A + sec A)2
= sin2 A + cosec2 A + 2sin A cosec A + cos2 A + sec2 A + 2cos A cot A
= (sin2 A + cos2 A) + (cosec2 A + sec2 A) + 2sin A * 1/sin A + 2cos A * 1/cos A
= 1 + 1 + cot2 A + 1 + tan2 A + 2 + 2
= 7 + cot2 A + tan2 A
= RHS
(ix) LHS:
(cosec A – sin A)(sec A – cos A) = (1/sin A – sin A)(1/cos A – cos A)
= {(1 – sin2 A)/sin A }{(1 – cos2 A)/cos A}
= {cos2 A)/sin A }{sin2 A)/cos A}
= sin A cos A …………..1
RHS:
1/(tan A + cot A) = 1/(sin A/cos A + cos A/sin A)
= 1/{(sin2 A + cos2 A)/(sin A cos A)}
= 1/{1/(sin A cos A)}
= sin A cos A ……………2
From equation 1 and 2, we get
(cosec A – sin A)(sec A – cos A) = 1/(tan A + cot A)
(x) LHS:
(1 + tan2 A)/(1 + cot2 A) = sec2 A/cosec2 A
= (1/cos2 A)/(1/sin2 A)
= sin2 A/cos2 A
= tan2 A
= RHS
Again (1 – tan A) 2/(1 – cot A) 2 = {(1 – tan A)/(1 – cot A)}2
= {(1 – sin A/cos A)/(1 – cos A/sin A)} 2
= [{(cos A – sin A)/cos A{/{(sin A – cos A)/sin A)}] 2
= [{(cos A – sin A)/cos A} * {sin A/(sin A – cos A)/sin A}] 2
= [-{(sin A – cos A)/cos A} * {sin A/(sin A – cos A)/sin A}] 2
= (-sin A/cos A)2
= sin2 A/cos2 A
= tan2 A
= RHS